RETRACTED: Recent New Results and Achievements of California South University (CSU) BioSpectroscopy Core Research Laboratory for COVID-19 or 2019-nCoV Treatment: Diagnosis and Treatment Methodologies of “Coronavirus” - Alireza, Heidari; Angela, Caissutti; Maria, Henderson; Katrina, Schmitt; Elizabeth, Besana; Jennifer, Esposito; Victoria, Peterson (Journal of Current Viruses and Treatment Methodologies, 2020)
Coronavirus nanoparticles show a strong peak of Plasmon absorption in ultraviolet–visible zone. A strong interaction exists between the surface of Coronavirus nanoparticles and Bcr–Abl tyrosine–kinase inhibitors (TKI) such as Imatinib (STI571), Nilotinib (AMN107), Dasatinib (BMS–345825), Bosutinib (SKI–606), Ponatinib (AP–24534) and Bafetinib (INNO–406). Bcr–Abl tyrosine–kinase inhibitors (TKI) such as Imatinib (STI571), Nilotinib (AMN107), Dasatinib (BMS–345825), Bosutinib (SKI–606), Ponatinib (AP–24534) and Bafetinib (INNO–406) cause to aggregation of Coronavirus nanoparticles linked to DNA/RNA and hence, lead to widening of peak Plasmon of Coronavirus nanoparticles surface at 550 (nm) and emerging a new peak at higher wavelength. In the current project, this optical characteristic of Coronavirus nanoparticles is used to time investigate of interaction between different Bcr–Abl tyrosine–kinase inhibitors (TKI) such as Imatinib (STI571), Nilotinib (AMN107), Dasatinib (BMS–345825), Bosutinib (SKI–606), Ponatinib (AP–24534) and Bafetinib (INNO–406) and Coronavirus nanoparticles. The results were shown that Bcr–Abl tyrosine–kinase inhibitors (TKI) such as Imatinib (STI571), Nilotinib (AMN107), Dasatinib (BMS–345825), Bosutinib (SKI–606), Ponatinib (AP–24534) and Bafetinib (INNO–406) with shorter chain length interact faster with Coronavirus nanoparticles. Therefore, a simple and fast method for identification of Bcr–Abl tyrosine–kinase inhibitors (TKI) such as Imatinib (STI571), Nilotinib (AMN107), Dasatinib (BMS–345825), Bosutinib (SKI–606), Ponatinib (AP–24534) and Bafetinib (INNO–406) with various chain length using red shift in surficial Plasmon absorption is presented.
Keywords: Bcr–Abl Tyrosine–Kinase Inhibitors (TKI); Peak Plasmon Absorption; Aggregation; Coronavirus Nanoparticles; DNA/RNA; Imatinib (STI571); Nilotinib (AMN107); Dasatinib (BMS–345825); Bosutinib (SKI–606); Ponatinib (AP–24534); Bafetinib (INNO–406)